Pemahaman Metrik dalam Membaca Notasi Balok - Silo Siswanto; Feri Firmansyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Abstract The ability to read beam notation at every level of education experiences constraints in terms of the accuracy measure of reading notation values, although in the subject matter the rhythm has been explained regarding the shape and value of notation. Therefore this study will provide metric formulations in the form of reading-symbols in measuring the short length value of sound in music notation, where the symbol is a solution in solving the intended problem. The formulation of this research problem, 1) How is the understanding of metrics which include rhythm, knock, and tempo in reading beam notation, 2) Why is the understanding of metrics important in reading beam notation, and 3) how is the formulation of metric formulas in the form of symbols in reading beam notation. While the specific objectives of this research are 1) Creating a formula about understanding metrics in reading beam notation. 2) Explain the importance of understanding metrics in reading beam notation. 3) Making symbols in reading beam notation. The method used in this study includes literature research and data collection is done through literature study and documentation related to western music theory. Furthermore, the analysis of data relating to western music theory is processed and formulated through musicology.Keywords: Matrix, Symbol How to Read, Beam Notation AbstrakKemampuan membaca notasi balok pada setiap tingkat pendidikan mengalami kendala dalam hal ukuran akurasi nilai notasi pembacaan, meskipun dalam materi pelajaran irama telah dijelaskan mengenai bentuk dan nilai notasi. Oleh karena itu penelitian ini akan memberikan formulasi metrik dalam bentuk membaca-simbol dalam mengukur nilai panjang pendek suara dalam notasi musik, dimana simbol merupakan solusi dalam menyelesaikan masalah yang dituju. Rumusan masalah penelitian ini, 1) Bagaimana pemahaman metrik yang meliputi ritme, ketukan, dan tempo dalam membaca notasi balok, 2) Mengapa pemahaman metrik penting dalam membaca notasi balok, dan 3) bagaimana formulasi rumus metrik dalam bentuk simbol dalam membaca notasi balok. Sedangkan tujuan khusus dari penelitian ini adalah 1) Membuat rumusan tentang memahami metrik dalam membaca notasi balok. 2) Jelaskan pentingnya memahami metrik dalam membaca notasi balok. 3) Membuat simbol dalam membaca notasi balok. Metode yang digunakan dalam penelitian ini termasuk penelitian kepustakaan dan pengumpulan data dilakukan melalui studi kepustakaan dan dokumentasi yang berkaitan dengan teori musik barat. Selanjutnya, analisis data yang berkaitan dengan teori musik barat diproses dan dirumuskan melalui musikologi.Kata kunci: Matriks, Simbol Cara Membaca, Notasi Balok